Brand Power: Analyzing the Synergy of Brand Image, Brand Ambassador, and Trust in E-Commerce - Julina, Julina; Meflinda, Astuti; Wicaksono, Karinda Putri (International Conference on Business Management and Accounting, 2024)
This study attempts to analyze the influence of brand image, brand ambassador, and trust on online shopping decisions. This study uses a quantitative approach with a survey method involving respondents who have shopped online in Indonesia. Data were collected through a questionnaire with a Likert scale and analyzed using the Partial Least Squares (PLS) technique. The results of the study indicate that brand image, brand ambassador, and trust have a positive and significant effect on online shopping decisions. In addition, brand image and brand ambassadors also have a positive and significant effect on trust. These findings indicate the importance of companies to strengthen brand image and choose the right brand ambassador to build consumer trust, so that it can encourage online purchasing decisions. This study contributes to a better understanding of consumer behavior in the context of e-commerce and strategic implications for digital marketing management